Insights from in vivo micro-CT analysis testing the hydraulic vulnerability segmentation in Acer pseudoplatanus and Fagus sylvatica seedlings - Losso, Adriano (The New phytologist, 2019)
© 2018 The Authors. New Phytologist © 2018 New Phytologist Trust.